Thalassotherapy dalam Konteks Kearifan Lokal: Studi Kasus Ritual Malukat di Pantai Mertasari Bali - Putut Dewantha Jenar (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This research analyzes the malukat ritual at Mertasari Beach, Sanur Kauh Village as a manifestation of Thalassotherapy within the context of Balinese local wisdom. Thalassotherapy, recognized as a healing method utilizing marine elements in modern medical practice, demonstrates alignment with the malukat ritual that has been practiced for generations by Balinese society. The research objectives are to identify Thalassotherapy elements within the malukat ritual, analyze underlying therapeutic mechanisms, and assess its effectiveness among practitioners. The study employs a qualitative approach with case study methodology, involving participatory observation, in-depth interviews with 14 informants comprising 2 spiritual leaders (pemangku) and 12 ritual practitioners, document analysis, and laboratory testing of seawater samples. Research findings reveal that the malukat ritual contains substantial Thalassotherapy elements, including body immersion in seawater, sea aerosol exposure, and climatotherapy utilization through morning sunlight. Laboratory analysis reveals NaCl content of 4.88% and Potassium 0.249 mg/L in Mertasari Beach seawater with therapeutic properties. Healing mechanisms operate through three synergistic dimensions: physicochemical (osmotic pressure and mineral content), psychoneurophysiological (neurohormonal modulation and sensory stimulation), and spiritual (positive autosuggestion and symbolic healing). The effectiveness of malukat ritual as a local Thalassotherapy method is evidenced through informant testimonies reporting improvements in physical, psychological, and spiritual conditions. This research concludes that local wisdom embedded in the malukat ritual possesses scientific validity aligned with modern Thalassotherapy concepts, thus demonstrating potential for development as an integrated, sustainable, and culturally-based health therapy alternative.